2005
DOI: 10.1111/j.1538-7836.2004.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐dimer levels during delivery and the postpartum

Abstract: Summary. Background: D-dimer (DD) measurement has proved to be very useful to exclude venous thromboembolism (VTE) in outpatients. However, during pregnancy, the progressive increase as well as the interindividual variations of DD means that in this instance they are of poor value to rule out VTE. Only a few studies have reported measurements of DD levels in the postpartum. Objectives: To measure DD sequentially in the puerperium in order to determine when DD levels return to values obtained in non-pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 21 publications
7
49
1
4
Order By: Relevance
“…The progressive increase in prenatal D-dimer levels during late gestation and the marked elevation soon after delivery seen in women with singleton pregnancies in this study were consistent with the results of earlier studies in singleton pregnancies Coagulation-fibrinolysis in twin pregnancies [9][10][11][12][13][14]. Our longitudinal study demonstrated that the prenatal plasma levels of D-dimer and FDP were consistently higher in women with twin pregnancies than in women with singleton pregnancies, although the deliveries took place approximately 2 weeks earlier in the twin group than in the singleton group.…”
Section: Discussionsupporting
confidence: 82%
“…The progressive increase in prenatal D-dimer levels during late gestation and the marked elevation soon after delivery seen in women with singleton pregnancies in this study were consistent with the results of earlier studies in singleton pregnancies Coagulation-fibrinolysis in twin pregnancies [9][10][11][12][13][14]. Our longitudinal study demonstrated that the prenatal plasma levels of D-dimer and FDP were consistently higher in women with twin pregnancies than in women with singleton pregnancies, although the deliveries took place approximately 2 weeks earlier in the twin group than in the singleton group.…”
Section: Discussionsupporting
confidence: 82%
“…È noto che i livelli dei D-dimeri aumentano molto in gravidanza: tale incremento si registra dalle prime settimane di gestazione fino al termine della gravidanza e nel post-partum, indipendentemente dal tipo di parto (vaginale o cesareo) [8,9]. L'aumento dei livelli di D-dimeri non è correlato al rischio clinico di trombosi nelle donne in gravidanza [10] pertanto, in questa situazione, non è utile fare ricorso alla valutazione del D-dimero per la diagnosi di trombosi venosa profonda o tromboembolismo polmonare.…”
Section: Stato Ipercoagulabile Correlato Alla Gravidanzaunclassified
“…Results of a small pilot study suggest that a strategy involving serial CUS combined with a moderately sensitive D-Dimer assay is effective in excluding DVT in pregnant women (27). D-Dimer levels are often positive in the later stages of pregnancy, (28,29) lowering the utility of this test to rule out DVT. Research to develop algorithms to diagnose DVT in pregnant women is ongoing.…”
Section: Diagnostic Algorithm For Dvtmentioning
confidence: 99%